Performance and mechanism of sinusoidal leading edge serrations for the reduction of turbulence–aerofoil interaction noise. (4th April 2017) - Chaitanya, P.; Joseph, P.; Narayanan, S.; Vanderwel, C.; Turner, J.; Kim, J. W.; Ganapathisubramani, B.
Abstract : This paper presents the results of a detailed experimental investigation into the effectiveness of sinusoidal leading edge serrations on aerofoils for the reduction of the noise generated by the interaction with turbulent flow. A detailed parametric study is performed to investigate the sensitivity of the noise reductions to the serration amplitude and wavelength. The study is primarily performed on flat plates in an idealized turbulent flow, which we demonstrate captures the same behaviour as when identical serrations are introduced onto three-dimensional aerofoils. The influence on the noise reduction of the turbulence integral length scale is also studied. An optimum serration wavelength is identified whereby maximum noise reductions are obtained, corresponding to when the transverse integral length scale is approximately one-fourth the serration wavelength. This paper proves that, at the optimum serration wavelength, adjacent valley sources are excited incoherently. One of the most important findings of this paper is that, at the optimum serration wavelength, the sound power radiation from the serrated aerofoil varies inversely proportional to the Strouhal number $St_{h}=fh/U$, where $f$, $h$ and $U$ are frequency, serration amplitude and flow speed, respectively. A simple model is proposed to explain this behaviour. Noise reductions are observed to generally increase with increasing frequency until the frequency at which aerofoil self-noise dominates the interaction noise. Leading edge serrations are also shown to reduce aerofoil self-noise. The mechanism for this phenomenon is explored through particle image velocimetry measurements. Finally, the lift and drag of the serrated aerofoil are obtained through direct measurement and compared against the straight edge baseline aerofoil. It is shown that aerodynamic performance is not substantially degraded by the introduction of the leading edge serrations on the aerofoil.